Defects in Persistent Luminescence Materials - Laamanen, Taneli (fi=Turun yliopisto|en=University of Turku|, 2011)
Persistent luminescence materials can store energy from solar radiation or artificial lighting and release it over a period of several hours without a continuous excitation source. These materials are widely used to improve human safety in emergency and traffic signalization. They can also be utilized in novel applications including solar cells, medical diagnostics, radiation detectors and structural damage sensors. The development of these materials is currently based on methods based on trial and error. The tailoring of new materials is also hindered by the lack of knowledge on the role of their intrinsic and extrinsic lattice defects in the appropriate mechanisms. The goal of this work was to clarify the persistent luminescence mechanisms by combining ab initio density functional theory (DFT) calculations with selected experimental methods. The DFT approach enables a full control of both the nature of the defects and their locations in the host lattice. The materials studied in the present work, the distrontium magnesium disilicate (Sr2MgSi2O7) and strontium aluminate (SrAl2O4) are among the most efficient persistent luminescence hosts when doped with divalent europium Eu2+ and co-doped with trivalent rare earth ions R3+ (R: Y, La-Nd, Sm, Gd-Lu). The polycrystalline materials were prepared with the solid state method and their structural and phase purity was confirmed by X-ray powder diffraction. Their local crystal structure was studied by high-resolution transmission electron microscopy. The crystal and electronic structure of the nondoped as well as Eu2+, R2+/3+ and other defect containing materials were studied using DFT calculations. The experimental trap depths were obtained using thermoluminescence (TL) spectroscopy. The emission and excitation of Sr2MgSi2O7:Eu2+,Dy3+ were also studied. Significant modifications in the local crystal structure due to the Eu2+ ion and lattice defects were found by the experimental and DFT methods. The charge compensation effects induced by the R3+ co-doping further increased the number of defects and distortions in the host lattice. As for the electronic structure of Sr2MgSi2O7 and SrAl2O4, the experimental band gap energy of the host materials was well reproduced by the calculations. The DFT calculated Eu2+ and R2+/3+ 4fn as well as 4fn-15d1 ground states in the Sr2MgSi2O7 band structure provide an independent verification for an empirical model which is constructed using rather sparse experimental data for the R3+ and especially the R2+ ions. The intrinsic and defect induced electron traps were found to act together as energy storage sites contributing to the materials’ efficient persistent luminescence. The calculated trap energy range agreed with the trap structure of Sr2MgSi2O7 obtained using TL measurements. More experimental studies should be carried out for SrAl2O4 to compare with the DFT calculations. The calculated and experimental results show that the electron traps created by both the rare earth ions and vacancies are modified due to the defect aggregation and charge compensation effects. The relationships between this modification and the energy storage properties of the solid state materials are discussed.